Penerapan Metode Rigging Pada Pembuatan Video Animasi 3D Bercocok Tanam Sayuran Hidroponik dan Non Hidroponik Menggunakan Unity - Ernanda Wijaya; Herlina Harahap; Dharmawati (Jurnal Ilmu Komputer dan Sistem Informasi, 2024)
Gardening and farming are the activities of planting and caring for plants for a specific purpose, such as to produce food, flowers, or medicinal plants. Gardening and farming are usually done in gardens, parks, or farmland. In gardening and farming, we need to understand various aspects, such as the type of plants to be planted, land preparation, planting techniques, plant maintenance, and also how to overcome problems that arise during the plant growth process. Indonesia has a fairly extensive greening program, there are still several problems related to greening in Indonesia, including: Lack of consistency in the implementation of greening programs, Lack of community support and understanding of the importance of greening, and others. This 3D animated video tutorial on farming organic, non-organic, and hydroponic plants with this rigging method is one effective way to provide information and education to the public about how to grow crops and gardening correctly and efficiently. The rigging method used in making this video allows the characters in the animation to move and interact naturally, so that the tutorial presented looks more lively and interesting. Basically, this animation video processing uses the Unity 3D application, and supporting applications such as Blender and SketchFab to obtain some of the assets needed. The result of the animated video created is in the form of a .mp4 file that can be played on various devices. Based on the test results that have been obtained, this animated video is very helpful for children and the community in farming and gardening.